2013
DOI: 10.7554/elife.00675
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptional response to ethylene gas drives growth hormone cross-regulation in Arabidopsis

Abstract: The gaseous plant hormone ethylene regulates a multitude of growth and developmental processes. How the numerous growth control pathways are coordinated by the ethylene transcriptional response remains elusive. We characterized the dynamic ethylene transcriptional response by identifying targets of the master regulator of the ethylene signaling pathway, ETHYLENE INSENSITIVE3 (EIN3), using chromatin immunoprecipitation sequencing and transcript sequencing during a timecourse of ethylene treatment. Ethylene-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
479
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(521 citation statements)
references
References 77 publications
(109 reference statements)
34
479
2
6
Order By: Relevance
“…For ABI5, ANAC055, and HB5 ChIP-seq, the YPET or wildtype lines were germinated and grown for 36 hr under dark or long day light conditions. ChIP-seq was carried out as previously described with minor modifications (Chang et al, 2013).…”
Section: Experimental Procedures Dap-seq and Chip-seq Experimentsmentioning
confidence: 99%
“…For ABI5, ANAC055, and HB5 ChIP-seq, the YPET or wildtype lines were germinated and grown for 36 hr under dark or long day light conditions. ChIP-seq was carried out as previously described with minor modifications (Chang et al, 2013).…”
Section: Experimental Procedures Dap-seq and Chip-seq Experimentsmentioning
confidence: 99%
“…An overview of which replicates were used for the samples is provided in Supplemental Table 4. For EIN3, the time point at which the maximal number of binding events occurred (4 h) was processed (Chang et al, 2013). REV, AMS, and FLP/MYB88 were removed from the data set due to a very low number of peaks in the results, the lack of paired-end read processing in the computational pipeline, and an abnormally high fraction of peak regions near transposable elements (Supplemental Figure 2A), respectively.…”
Section: Chip-seq Processingmentioning
confidence: 99%
“…RAP2.3 represents an EIN3-dependent branch of ethylene signaling, formerly exemplified by ERF1 (Solano et al, 1998), which participates in the transcriptional cascade triggered by the hormone in the control of this developmental process. RAP2.3 regulates sets of genes that are not directly regulated by EIN3, which is the case of three of four genes shown in Figure 4 (Chang et al, 2013), expanding this way the effect on gene expression triggered by ethylene. Interestingly, HLS1, a major target of EIN3 in the regulation of hook development, is not an in vivo target of RAP2.3, because (1) its expression was not altered after RAP2.3 induction or in the rap2.3 mutant (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that RAP2.3 expression is induced by ethylene (Büttner and Singh, 1997). Significantly, EIN3 binds in vivo to the RAP2.3 promoter (Chang et al, 2013) and activates its expression in etiolated seedlings (Fig. 6A), suggesting that RAP2.3 could also participate in the mechanism regulating apical hook development by GAs and ethylene.…”
Section: Dellas Prevent the Binding Of Rap23 To The Promoter Of Itsmentioning
confidence: 99%
See 1 more Smart Citation